Non-Motor Symptoms of Essential Tremor Are Independent of Tremor Severity and Have an Impact on Quality of Life. (8th March 2016) - Musacchio, Thomas; Purrer, Veronika; Papagianni, Aikaterini; Fleischer, Anna; Mackenrodt, Daniel; Malsch, Carolin; Gelbrich, Götz; Steigerwald, Frank; Volkmann, Jens; Klebe, Stephan
Background: Several publications have focused on accompanying non-motor symptoms (NMS) in essential tremor (ET) patients; however, it remains unclear if NMS are an intrinsic part of the disease or secondary phenomena. We present the results of several neuropsychiatric tests and their impact on quality of life (QoL) in community-dwelling patients with ET. Methods: Participants were recruited via a newspaper article about ET published in the local media and on the internet. All participants completed several standard neuropsychiatric tests, including those that assess QoL. To compare differences between cases and controls, Student's t -tests with Bonferroni-Holm post hoc tests were performed. Spearman's correlation coefficients were also calculated. Results: We enrolled 110 patients with definite or probable ET. Highly significant changes were observed for apathy, anxiety, and cognition and negatively impacted QoL. Most aberrations were independent of tremor severity and duration. Discussion: The significant neuropsychiatric deficits and reduced QoL demonstrate a degree of illness that appears to be a non-motor phenotype rather than a secondary effect of ET. In the future, NMS should carefully be explored in ET patients as they may have an impact on QoL and treatment.